Protein Profile and Decolorization Potential of Copper-Resistant Klebsiella pneumonia CKJ 500 2.1.2 in Response to Textile Dyes and Copper - Irawati, Wahyu; Pinontoan, Reinhard; Marcellie, Jessica; Valiant, Andreas; Sugata, Marcelia (Bogor Agricultural University, Indonesia, 2026)
Heavy metals and synthetic dyes are major environmental pollutants, particularly in industrial effluents. The development of effective and safe bioremediation strategies to mitigate their ecological impact is therefore critical. In this study, the copper-resistant bacterium Klebsiella pneumoniae CKJ 500 2.1.2 was investigated for its capacity to decolorize textile dyes—specifically malachite green—and its associated enzymatic activities were characterized. Bacterial resistance was assessed using Luria–Bertani agar containing varying concentrations of copper and dyes. Decolorization efficiency was evaluated spectrophotometrically, protein expression was analyzed using SDS-PAGE, and dye degradation products were identified using gas chromatography–mass spectrometry (GC-MS). The strain exhibited high tolerance to both copper and dyes, achieving 99.4% decolorization of malachite green and 81% for Congo red. The presence of copper inhibited the decolorization of most dyes, except malachite green and methylene blue. SDS-PAGE analysis identified three key enzymes: laccase ( 60 kDa), manganese peroxidase ( 39 kDa), and azoreductase ( 22 kDa). GC-MS revealed both toxic and non-toxic degradation intermediates, indicating partial detoxification. These findings highlight the potential of K. pneumoniae CKJ 500 2.1.2 for bioremediation of dye-contaminated effluents. However, further research is required to elucidate the complete enzymatic pathways involved and to ensure environmentally safe dye degradation.